Analisis Implementasi Smart Society melalui Program Gerbang Hebat di Kota Semarang - Agustina Rahmawati; Hanantyo Sri Nugroho (Jurnal Public Policy, 2021)
Joint movement for poverty and unemployment reduction through harmonization of the economy, education, ecosystems and community ethos, or abbreviated Gerbang Hebat of the Semarang City Government, which was pursued in Semarang City has achieved a significant poverty reduction effort of at least 1.5% per year in accordance with the RJMD target of Semarang City in 2016-2021. The Semarang City Government in implementing the Gerbang Hebat Program joins hands with all stakeholders, namely BUMN, BUMD, Banking, Business, Private Sector, State and Private Universities, NGOs and community organizations to jointly make efforts to improve community welfare. Based on this, this study analyzes the implementation of the Gerbang Hebat program by observing the phenomenon of the implementation of program policies, namely the driving and inhibiting factors in the implementation of the Gerbang Hebat program in an effort to create an intelligent community in the city of Semarang. The approach used is a descriptive qualitative method where data collection uses interviews, observation, and documentation studies. The results of this study are the presentation of a valid, accurate, right on target, objective, and up to date database where name-based address and potential and area are still a challenge and monitoring and evaluation when the program is completed. In addition, community participation has an important role in realizing digital-based community governance. This is to ensure that activities are in accordance with the needs of the community, and ensure that these activities are sustainable activities and can lead the community towards independence.